THE EFFECT OF Rhizopus sp TO MAKE COCONUT OIL ON ITS QUALITY - Wiadnya, Ida Bagus Rai; Urip, Urip; Minovriyanti, Eka (Jurnal Analis Medika Biosains (JAMBS), 2014)
AbstractFermented coconut oil is the oil extracted from coconuts and if the fermentation is catalyzed by the microorganisms in the process of separating the oil from carbohydrates and protein found in the endosperm cells of seeds coconut. Making coconut oil by fermentation is done without heating, but with the addition of yeast in cream coconut  and then incubated for 24 hours at a temperature of 300C to precipitate and form a layer of oil on the surface.To determine the effect of tempe (Rhizopus sp) on the quality of oil is the determination of the levels of acid number and saponification-titration method asidi alkalimetry.Research is Pre experimental post-test only design approach. By study design completely randomized design (CRD) with 5 treatments and 5 replications.The average level of lowest acid number obtained on the addition of 2 grams of yeast / liter of coconut cream at 0.2968 mg KOH / grams and the highest in the addition of 6 grams of yeast / liter of coconut cream at 0.4562 mg KOH / grams, while the the average level of lowest saponification obtained on addition of yeast 2 grams / liter of coconut cream at 261.106 mg KOH / grams and the highest in the addition of 6 grams of yeast / liter of coconut cream at 262.804 mg KOH / gFrom the results of statistical tests, values obtained for acid number p = 0.034 <α = 0.05, meaning that there is the effect of adding tempe (Rhizopus sp) to the acid number. And for saponification p = 0.06> α = 0.05 means that there is no effect of the addition of tempe (Rhizopus sp) on saponification.Keywords: Yeast Tempe, Fermented Coconut Oil, Oil Quality